Role of HDAC6 and Its Selective Inhibitors in Gastrointestinal Cancer - Zhou, Bingyi; Liu, Deliang; Tan, Yuyong (Frontiers in Cell and Developmental Biology, 2021)
Worldwide, cancer is the second leading cause of mortality after cardiovascular diseases. Among the numerous malignant tumors in human, digestive system cancers are the primary cause of morbidity and mortality. Acetylation and deacetylation are crucially involved in cancer occurrence and development; additionally, the deacetylation process is regulated by histone deacetylases (HDACs). Among the 18 human HDACs that have been reported, HDAC6 has been widely studied. There is upregulated HDAC6 expression in numerous types of tumor tissues and is closely associated with clinicopathological characteristics. Moreover, several HDAC6 inhibitors have been identified; further, there has been extensive research on their ability to inhibit the growth of many tumors. This review summerizes the roles of HDAC6 in different primary digestive system malignancies.